2016
DOI: 10.1080/10803548.2015.1117352
|View full text |Cite
|
Sign up to set email alerts
|

Impact of error self-perception of aerobic capacity in the safety and efficacy of the lifeguards

Abstract: This self-perception error of true aerobic capacity could lead to premature fatigue during a rescue, endangering both the lifeguard's life and the life of the victim. These data may help lifeguards and beach managers to become aware of the need to know lifeguards' true physical conditions through testing and structured training programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…In the current study the results of VO2Max obtained during the laboratory test confirmed a high level of physical condition in the sample studied. The mean values recorded were higher than the recommended minimum for the aptitude of professional lifeguards (Prieto, Nistal, Méndez, Abelairas-Gomez, & Barcala-Furelos, 2015). The results were similar to those found in previous studies of other rescue workers (Prieto et al, 2010, Salvador et al, 2014 and higher than those achieved by other rescue groups such as firefighters or first responder groups (Prieto, González, Del Valle, & Nistal, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…In the current study the results of VO2Max obtained during the laboratory test confirmed a high level of physical condition in the sample studied. The mean values recorded were higher than the recommended minimum for the aptitude of professional lifeguards (Prieto, Nistal, Méndez, Abelairas-Gomez, & Barcala-Furelos, 2015). The results were similar to those found in previous studies of other rescue workers (Prieto et al, 2010, Salvador et al, 2014 and higher than those achieved by other rescue groups such as firefighters or first responder groups (Prieto, González, Del Valle, & Nistal, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…One of the most important factors to take into consideration when performing a water rescue is the physical condition of lifeguards, determined by the physiological demands of the rescue. In this sense, it has been shown that the values of heart rate [6,7], blood lactate [8,9] and oxygen uptake [10] increase until they approach maximum values during a rescue, which means that aerobic capacity and power are fundamental to the lifeguard's performance during the rescue [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Lifeguards require a high level of physical conditioning to respond to the physiological demands of a water rescue [1]. Drowning is a global health problem, which in 2017 caused 295,210 drowning deaths [2], a number that would be much higher without lifeguard prevention and rescues.…”
Section: Introductionmentioning
confidence: 99%